Efektivitas Latihan Range of Motion (ROM) Terhadap Kekuatan Otot Pada Penderita Stroke - Parmin, Selamat; Safitri, Serli Wulan; Morens, Devia (Yayasan Daarul Huda Kruengmane, 2023)
Stroke is a condition that occurs when the blood supply to a part of the brain is suddenly disrupted, because some brain cells die due to impaired blood flow due to blockage or rupture of blood vessels in the brain. The purpose of this study was to determine the effect of